2022
DOI: 10.30541/v55i4i-iipp.689-702
|View full text |Cite
|
Sign up to set email alerts
|

Corruption, Political Stability and Economic Growth

Abstract: This paper gives insight of the role of political stability in investigating the two competing hypotheses in Developing Eight Muslim countries, and also investigates whether conditional liaison between corruption and political stability matters or not. The empirical findings indicate that investment, population and political stability play positive role in promoting economic growth. Corruption not only impact growth but also influenced by the institutional quality that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…With stable political conditions, democratic government regimes, and safe state conditions will give perceptions of investors to invest in the country and create jobs so that economic growth can be increased. The finding of this study agrees the finding of Shabbir et al (2016) and Omoteso and Mobolaji (2014), while rejecting the findings of Adefeso (2018).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…With stable political conditions, democratic government regimes, and safe state conditions will give perceptions of investors to invest in the country and create jobs so that economic growth can be increased. The finding of this study agrees the finding of Shabbir et al (2016) and Omoteso and Mobolaji (2014), while rejecting the findings of Adefeso (2018).…”
Section: Resultssupporting
confidence: 78%
“…Study results of Shabbir, Anwar, and Adil (2016) shows that political stability can reduce social unrest, political turmoil, and encourage investment so that economic growth can be increased. In contrast to study Adefeso (2018) which concluded that political stability and corruption have no significant effect on economic growth in African region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of this study are the opposite, the corruption has no effect on economic growth. supporting research conducted by Tseng (2020) concludes that corruption in a emerging country has no impact on economic growth, it is concluded that not all corruption has a bad effect on the economy (Fernández-Torres et al, 2018;Sasti & Latrini, 2019;Shabbir et al, 2016;Tseng, 2020). Corruption with the characteristic of "speed money" or "grease the wheel" has a positive effect on economic growth.…”
Section: Results and Analysismentioning
confidence: 99%
“…Research by Tseng (2020), also examined the effects of corruption on economic growth and the results were the same, namely that the decline in corruption in a emerging country, had no impact on economic growth, on the contrary, it concluded that not all corruption had a bad effect on the economy. Corruption which had the characteristic "speed money" had a positive effect on economic growth (Fernández-Torres et al, 2018;Sasti & Latrini, 2019;Shabbir et al, 2016;Tseng, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nurudeen et al (2015) find a unidirectional causality from political instability to economic growth in the short-term while in the long-term causality runs from growth and political stability to corruption. Shabbir et al (2016) find that corruption determines both economic growth and institutional quality.…”
Section: Topics In Middle Eastern and North African Economies Proceedmentioning
confidence: 98%